The negative effect of Akkermansia muciniphila-mediated post-antibiotic reconstitution of the gut microbiota on the development of colitis-associated colorectal cancer in mice - Wang, Kaicen; Wu, Wenrui; Wang, Qing; Yang, Liya; Bian, Xiaoyuan; Jiang, Xianwan; Lv, Longxian; Yan, Ren; Xia, Jiafeng; Han, Shengyi; Li, Lanjuan (Frontiers in Microbiology, 2022)
The bidirectional relationship between colorectal cancer (CRC) and the gut microbiome has been well-documented. Here, we investigated the impact of Akkermansia muciniphila-mediated post-antibiotic gut microbial reconstitution on the development of colitis-associated CRC (CAC). The results showed that post-antibiotic replenishment of A. muciniphila worsened the tumorigenesis of CAC as indicated by increased number of large (>2 mm in diameter) tumors and both average and total tumor diameters. Measures of intestinal barrier function showed that post-antibiotic A. muciniphila gavage damaged the intestinal barrier as reflected by lower transcriptional levels of Tjp1, Ocln, Cdh1, and MUC2. Impaired gut barrier was followed by lipopolysaccharides (LPS) translocation as indicated by higher level of serum LPS-binding protein (LBP). The increased colonic mRNA levels of Il1b, Il6, and Tnfa and serum levels of IL-1β, IL-6, and TNF-α indicated that post-antibiotic A. muciniphila replenishment resulted in overactivated inflammatory environment in CAC. The analysis of the evolution of the microbial community during the progression of CAC showed that post-antibiotic supplementation of A. muciniphila led to a distinct microbial configuration when compared with other treatments characterized by enriched Firmicutes, Lachnospiraceae, and Ruminococcaceae, and depleted Bacteroidetes, which was accompanied by higher Firmicutes/Bacteroidetes (F/B) ratio. Furthermore, post-antibiotic A. muciniphila administration changed the bile acid (BA) metabolic profile as indicated by decreased concentrations of secondary BA (SBA), ω–murocholic acid (ωMCA), and murocholic acid (muroCA). In addition, the A. muciniphila supplementation after antibiotic pretreatment also impacted the metabolism of short-chain fatty acids (SCFAs) as evidenced by increased concentrations of acetic acid, propionic acid, butyric acid, and valeric acid. Our study surprisingly observed that A. muciniphila-mediated post-antibiotic reconstitution of the gut microbiota aggravated the CAC in mice. It might exert its effect by damaging the gut barrier, exacerbating inflammatory responses, disrupting the post-antibiotic recovery of the microbial community, and further influencing the metabolism of BA and SCFAs. These findings indicated that maintaining the homeostasis of intestinal microorganisms is more crucial to health than replenishing a single beneficial microbe, and probiotics should be used with caution after antibiotic treatment.